(untitled) (Research, Society and Development, 2021)
This review aims to present evidence as to the relevance of pharmacotherapeutic monitoring provided to patients with type 2 diabetes mellitus treated in community pharmacies, in addition to knowing the role of community pharmacists in the control of type 2 diabetes and investigating the positive aspects of pharmacotherapeutic monitoring aimed at diabetic patients. This is a literature review carried out by searching for original articles in databases such as Scielo, PubMed and Lilacs. The inclusion criteria were: publications that met the proposal of the theme, complete articles, in portuguese and published from 2010 to 2019. The exclusion criteria were: incomplete studies, which did not meet the objective and theme of the research, in addition to books, dissertations and theses. The articles that made up the review showed that the main doubts of patients with DM were related to the times of administration of the medications. Other findings showed that there was good acceptability of the proposal for pharmacotherapeutic follow-up and that its applicability in private community pharmacies brings several benefits such as greater adherence to treatment, occurring rationally with improved clinical results and establishing a link between pharmacist and user, reaffirming the capacity pharmacist to carry out clinical activities in the private sector. This study made it clear that the practice of pharmaceutical care and good dispensing practices aimed at patients treated in drugstores can be achieved without the need for major structural changes in the establishment and without hiring additional staff.